Peer Facilitators as Core Co-developers of an Online Peer Encouragement Network (OPEN2chat) for Austrian Adolescents - Mittmann, Gloria; Schmalwieser, Susanne Sophie; Diendorfer, Tamara; Schrank, Beate; Boeckle, Markus (Frontiers in Digital Health, 2022)
Adolescence is a crucial developmental time, and it is essential to ensure stable mental health during the transition to adulthood. Peer-to-peer networks seem to be a promising tool to support adolescents during that time. While co-development often concentrates on the end-user, this paper focuses on the peer facilitators of an online peer encouragement network (OPEN2chat) where adolescents can chat with peer facilitators about their problems. We conducted 3 group discussions with 18 peer facilitators after a testing phase to improve the process of these interactions. Thematic analysis was used to analyse the data after transcription. The four main themes were the responsibility of the peer facilitators towards their peers, especially their role of giving advice; the interaction process itself; time management; and technology aspects of the application. Including these stakeholders in the development process empowered these young people, helped eliminate problems with the application, and made the researchers more sensitive towards potential issues and emotions that peer facilitators encounter that may have been missed without a co-development process. Eliminating these problems might also help establish a better environment and support system for the actual end-users.